2008
DOI: 10.1002/ase.48
|View full text |Cite
|
Sign up to set email alerts
|

Performance in a prematriculation gross anatomy course as a predictor of performance in medical school

Abstract: The University of California at Davis School of Medicine offers a prematriculation program to nontraditional students. As part of the program, students take a 7-day course on the gross anatomy of the upper limb that concludes with a written examination and a practical examination based on prosections. Here, the performance of students who took the course from 2002 to 2004 (n = 48) is compared with their performance in the medical gross anatomy course as well as their performance on Step 1 of the United States … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 10 publications
0
9
0
2
Order By: Relevance
“…A veterinary school study (McNulty et al, ) demonstrated that students with summer pre‐matriculation coursework not only scored better on the repeated material in veterinary gross anatomy, but the gains also carried over to improved performance over non‐participating students on subsequent gross anatomy examinations. Tucker () demonstrated that not only can a pre‐matriculation course significantly predict performance in a medical gross anatomy course, but it also correlated to USMLE ® Step 1 examination scores. Lu and Notebaert () did not relate pre‐matriculation participation to course grades in medical or dental school; however, they showed that the participation in the summer course supported student study habits, encouraging students to choose deep approaches to anatomy learning in the summer just prior to medical or dental school.…”
Section: Introductionmentioning
confidence: 99%
“…A veterinary school study (McNulty et al, ) demonstrated that students with summer pre‐matriculation coursework not only scored better on the repeated material in veterinary gross anatomy, but the gains also carried over to improved performance over non‐participating students on subsequent gross anatomy examinations. Tucker () demonstrated that not only can a pre‐matriculation course significantly predict performance in a medical gross anatomy course, but it also correlated to USMLE ® Step 1 examination scores. Lu and Notebaert () did not relate pre‐matriculation participation to course grades in medical or dental school; however, they showed that the participation in the summer course supported student study habits, encouraging students to choose deep approaches to anatomy learning in the summer just prior to medical or dental school.…”
Section: Introductionmentioning
confidence: 99%
“…After an extensive Medline literature search, not a single study was found correlating performance in Anatomy (or any other basic science subject) with clinical skills proficiency. There were a few studies in the literature (all from the same medical school in the United States) which described the use of Anatomy as a positive predictor of performance in US medical schools and in the United States Medical Licensing Examination (USMLE) Step I licensing examination (Peterson and Tucker, 2005a, b; Tucker, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A la luz de lo expuesto, resulta interesante considerar la evidencia internacional reciente que señala que el rendimiento en los cursos de anatomía constituye un excelente predictor en relación con el desempeño en el examen de licencia médica, el equivalente a nuestro examen médico nacional (Peterson & Tucker, 2005;Tucker, 2008); todo ello avalado por una metodología de enseñanza en la cual se desarrollan en los estudiantes las habilidades cognitivas necesarias, utilizando un aprendizaje exploratorio donde puedan correlacionar la anatomía con diagnósticos clínicos. Por esto, es importante considerar aquellos contenidos clínicamente relevantes y que les sean útiles para la introducción temprana de esta habilidades prácticas en el pabellón de anatomía (Philip et al, 2008).…”
Section: Discussionunclassified